Optimization of Nutrition Therapy with the Use of Calorimetry to Determine and Control Energy Needs in Mechanically Ventilated Critically Ill Patients: The ONCA Study, a Randomized, Prospective Pilot Study. Issue 4 (25th September 2018) - Gonzalez‐Granda, Anita; Schollenberger, Asja; Haap, Michael; Riessen, Reimer; Bischoff, Stephan C.
Abstract: Background: Adequate nutrition therapy in critically ill patients poses a challenge because of the variable energy and substrate needs. The objective was to investigate whether nutrition therapy involving indirect calorimetry (IC), instead of equations for assessment of energy needs, could improve the nutrition status of critically ill patients. Methods: Forty mechanically ventilated patients were randomized into a group in which energy needs were controlled by calorimetry (IC group) and a group treated with a formula‐based approach reflecting standard care (SC group). The primary outcome was change in the phase angle (PhA), a bioelectrical impedance parameter related to nutrition status and prognosis. Results: The mean IC‐based energy requirement was lower than the formula‐based estimate (21.1 ± 6.4 versus [vs] 25 kcal/kg/d, P < .01). The IC group reached 98% ± 8% of the energy goal, whereas the SC group reached only 79% ± 29% ( P < 0.05), although mean intake was similar in both groups. The protein intake goal was better met in the IC group (91% ± 24%) than the SC group (73% ± 33%). The PhA of the IC group did not change during treatment, whereas that of the SC group tended to decrease by 0.36° ± 0.86° ( P = .077). A shorter length of stay in intensive care was observed in the IC than in the SC group (13 ± 8 vs 24 ± 20 days, P < .05). Conclusion: Intensified individual nutrition therapy involving IC appears to be useful for improving nutrition status in critically ill patients.